2009
DOI: 10.1111/j.1526-4637.2009.00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 5-Day Continuous Lidocaine Infusion for the Treatment of Refractory Complex Regional Pain Syndrome

Abstract: Intravenous lidocaine administration titrated to 5 mg/L demonstrated: 1) a significant decrease in mechanical and thermal allodynia for three months, 2) lessened associated inflammatory components of CRPS, and 3) only minimal side effects and no severe complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 49 publications
(56 reference statements)
2
46
0
Order By: Relevance
“…One RCT found significant improvement in all pain parameters with a 5-mg/kg infusion; 17 a retrospective study of 49 CRPS patients found that 76% had at least 25% pain reduction 3 months after a 5-day lidocaine infusion. 18 …”
Section: Anestheticsmentioning
confidence: 97%
“…One RCT found significant improvement in all pain parameters with a 5-mg/kg infusion; 17 a retrospective study of 49 CRPS patients found that 76% had at least 25% pain reduction 3 months after a 5-day lidocaine infusion. 18 …”
Section: Anestheticsmentioning
confidence: 97%
“…However, prolonged relief has been reported in animal models [274] and in some non-randomized [255,275] and randomized trials [175,276,277]. The Canadian Pain Society states that "intravenous lidocaine infusions are generally safe and can provide significant pain relief for 2-3 weeks at a time" [278].…”
Section: Selection Criteria For the Use Of Ivlt In Paediatric Chronicmentioning
confidence: 99%
“…Early recognition and appropriate '3P' management is the key to success. Within the context of the coordinated multi-disciplinary approach, IVLT can serve as a useful adjunct to concurrent physical, and psychological interventions to manage chronic pain in children and youths [133,254,255]. IVLT needs to be explained and utilized in a way that does not negate the multi-disciplinary teams attempts to promote self-management and de-medicalization.…”
Section: Multi-disciplinary Team Management Of Children With Chronic mentioning
confidence: 99%
See 1 more Smart Citation
“…She has been treated with both ketamine and lidocaine infusions for her CRPS. 5,6 The ketamine has shown benefit in terms of decreasing the diffuse erythema and swelling which occur intermittently over her entire body and face. Lidocaine infusions produce some relief of her pain.…”
Section: Introductionmentioning
confidence: 99%